2017
DOI: 10.1111/hel.12390
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Helicobacter pylori tfs plasticity zone cluster is regulated by pH and adherence, and its composition is associated with differential gastric IL‐8 secretion

Abstract: A complete tfs plasticity zone cluster is a virulence factor that may be important for the colonization of H. pylori and to the development of severe outcomes of the infection with cagA-positive strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
(113 reference statements)
0
19
0
Order By: Relevance
“…They generally contain complete sets of genes required to produce T4SS protein, as well as genes encoding different DNA processing proteins . A complete T4SS plasticity zone cluster is known to be a virulence factor that may be important for the colonization of H. pylori- and development of severe outcomes of infection with cagA‐positive strains . Additionally, genes encoding T4SS proteins can be transferred by conjugation between Rhizobium radiobacter and Bartonella rattaustraliani .…”
Section: Discussionmentioning
confidence: 99%
“…They generally contain complete sets of genes required to produce T4SS protein, as well as genes encoding different DNA processing proteins . A complete T4SS plasticity zone cluster is known to be a virulence factor that may be important for the colonization of H. pylori- and development of severe outcomes of infection with cagA‐positive strains . Additionally, genes encoding T4SS proteins can be transferred by conjugation between Rhizobium radiobacter and Bartonella rattaustraliani .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the H. pylori TFSS plasticity zone cluster showed that the whole composition of TFSS in association with CagA positivity may induce higher IL‐8 during cell line co‐culture and was influenced by adherence and pH of infection . Lastly, a single operon was found to regulate the expression of its component spanning from VirB2 to VirB10 …”
Section: Virulence Factorsmentioning
confidence: 99%
“…25 Analysis of the H. pylori TFSS plasticity zone cluster showed that the whole composition of TFSS in association with CagA positivity may induce higher IL-8 during cell line co-culture and was influenced by adherence and pH of infection. 26 Lastly, a single operon was found to regulate the expression of its component spanning from VirB2 to VirB10. 26 27 While urease appeared to be less essential after established colonization, chronic infection was restored by a positive selection process that altered the repressor protein, supporting a continual requirement for urease.…”
Section: Non-cag Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the NUD and PUD H. pylori pediatric strains were genotyped for the presence/status of babA, babB, babC, cagA, vacAsallele, hopQ allele, oipA, sabA, hopZ, and homB outer membrane protein encoding genes (Table 1) by whole genome sequencing (WGS), considering the previously published 12 H. pylori genomes [44,45], and eight new genomes, that were sequenced on a MiSeq Illumina platform, as previously described [45]. Briefly, high-quality genomic DNA samples from pure bacterial cultures were used to prepare Nextera XT Illumina libraries that were sequenced on an Illumina MiSeq platform (Illumina Inc., San Diego, CA) using the v.2 (300 cycles, 2×150 nt reads or 500 cycles, 2×250 nt reads) kit, according to the manufacturer's instructions.…”
Section: Genotyping Of H Pylori Virulence Genesmentioning
confidence: 99%